2018
DOI: 10.22616/erdev2018.17.n347
|View full text |Cite
|
Sign up to set email alerts
|

Composite sandwich-type panel made of foamgypsum

Abstract: Sandwich type panels are popular building materials with low weight and high strength. Sandwichtype panels nowadays are mostly used in high thickness as elements for external walls or roofs. But in most cases modern building panels contain lots of combustible additives, which can produce toxic fumes and expedite fire in buildings. In this paper, sandwich-type panels are discussed with structural, acoustic, fire and heat insulation properties made of foamed gypsum core with an open and close cellular structure … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 7 publications
1
3
0
Order By: Relevance
“…5). This does not differ from practical data, well known from works [4,7], the authors of which also associate the effectiveness of fire protection with the formation of a layer of pinocoke during the decomposition of the coating under the influence of the burner flame. But, in contrast to the results of research reported in [17,18], our data on the effect of the swelling coating on the process of retarding the transfer of temperature allow us to state the following:…”
Section: Features Of Reducing the Degree Of Burnout Of A Fire-resista...supporting
confidence: 58%
See 1 more Smart Citation
“…5). This does not differ from practical data, well known from works [4,7], the authors of which also associate the effectiveness of fire protection with the formation of a layer of pinocoke during the decomposition of the coating under the influence of the burner flame. But, in contrast to the results of research reported in [17,18], our data on the effect of the swelling coating on the process of retarding the transfer of temperature allow us to state the following:…”
Section: Features Of Reducing the Degree Of Burnout Of A Fire-resista...supporting
confidence: 58%
“…Paper [7] deals with sandwich panels with structural, sound, fire, and thermal insulation properties, made of a foamed gypsum core with an open and closed cellular structure and facing of increased strength on both sides from ordinary plasterboard. Gypsum is used as a fire and acoustic material with excellent fire protection because it dehydrates at temperatures around 100 °C, absorbing energy and acting as a thermal barrier.…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%
“…Modern constructions and large products are often produced of prefabricated multi-layered mechanical structures, which exhibit high specific stiffness, strength, environmental resistance and thermal insulation characteristics [2,3]. Such mechanical structures are widely used in residential and industrial buildings [4,5], thermal and nuclear power stations, space stations, ships [6][7][8] and airplanes [9].…”
Section: Introductionmentioning
confidence: 99%
“…Gypsum is a natural, cheap, and ecologic raw material, which provides excellent fire protection because it dehydrates at a temperature around 100°C absorbing energy and acting as a heat barrier [3]. However, the dehydration process severely deteriorates its integrity causing the material to lose most of the ambient temperature strength [1,13].…”
Section: Introductionmentioning
confidence: 99%